A new art from emerging markets - Robertson, Iain (Iain Alexander) (Surrey, United Kingdom Burlington, Vermont Lund Humphries, 2011)
A New Art From Emerging Markets sets out to introduce and examine three types of emerging market for contemporary art: the very recently established, the maturing and the mature. In temporal terms, the youngest are no more than five years old; the maturing, fifteen years old; and the mature up to twenty-five years old.
Introduction: All change in the art market -- The East Asian democracies: Taiwan, South Korea and Japan -- Greater China -- The Persianate world: Iran, Iraq, Pakistan and Afghanistan -- Hindustan: India -- South East Asia: Indonesia, Thailand, Vietnam, Philippines and Malaysia -- The offshore art exchanges: Hong Kong, Singapore and the United Arab Emirates.
Includes bibliographical references (p. 200-205) and index.
Keywords: Art, Modern -- 20th century -- Economic aspects; Art, Modern -- 21st century -- Economic aspects; Art, Asian -- 20th century; Art, Asian -- 21st century; Art and society -- Asia; Art and state -- Asia